Penerapan Metode Token Ekonomi pada Nn. Ns Dengan Defisit Perawatan Diri di Ruangan Kabela RSJ. Prof. Dr. V. L. Ratumbuysang Provinsi Sulawesi Utara - Pangalila, Dewini Wahyuni Pratiwi; Buanasari, Andi; Bidjuni, Hendro Joli Bidjuni (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2024)
Background: Self-care deficits are a common issue among schizophrenia patients. The impact of these deficits disrupts patients' performance in activities, leading to a poor quality of life. Objective: This case study aims to assess the effectiveness of the token economy method in improving self-care deficits in schizophrenia patients. Method: The case study employs the token economy method in nursing care, involving the provision of tokens that can be exchanged for rewards as a form of appreciation for the patient's behavior. Results: Prior to the intervention, the total self-care score was only 3 points, while after the intervention, the total self-care score increased to 18 points. Discussion: The patient was able to perform self-care activities such as bathing and grooming gradually and could establish good habits. Conclusion: The patient benefited from the token economy intervention, which led to positive behaviors, including increased self-confidence in social interactions. Keywords: economic tokens; nursing care; self-care deficit.